2005
DOI: 10.1139/g05-028
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 2 intraspecific linkage maps and identification of resistance QTLs forPhytophthora capsiciroot-rot and foliar-blight diseases of pepper (CapsicumannuumL.)

Abstract: Two linkage maps of pepper were constructed and used to identify quantitative trait loci (QTLs) conferring resistance to Phytophthora capsici. Inoculations were done with 7 isolates: 3 from Taiwan, 3 from California, and 1 from New Mexico. The first map was constructed from a set of recombinant inbred lines (RILs) of the PSP-11 (susceptible) x PI201234 (resistant) cross; and the second map was from a set of F(2) lines of the Joe E. Parker' (susceptible) x 'Criollo de Morelos 334' (resistant) cross. The RIL map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 34 publications
8
58
3
4
Order By: Relevance
“…S19 was mapped to P9, $6 cM below TG263 and centromeric with respect to the position for the 1-kb band of A2 (Figure 6), demonstrating that Bs2 resides on P9 in a region of the pepper genome that is orthologous to the top arm of potato XII that includes the fractionated orthologs Rx and Gpa2. This is consistent with results from others who have located several PCR markers with similarity to Bs2 on this chromosome (Ogundiwin et al 2005;Sugita et al 2006;DjianCaporalino et al 2007).…”
Section: Resultssupporting
confidence: 93%
“…S19 was mapped to P9, $6 cM below TG263 and centromeric with respect to the position for the 1-kb band of A2 (Figure 6), demonstrating that Bs2 resides on P9 in a region of the pepper genome that is orthologous to the top arm of potato XII that includes the fractionated orthologs Rx and Gpa2. This is consistent with results from others who have located several PCR markers with similarity to Bs2 on this chromosome (Ogundiwin et al 2005;Sugita et al 2006;DjianCaporalino et al 2007).…”
Section: Resultssupporting
confidence: 93%
“…Linkage analysis revealed that many molecular markers were located at the same loci: 224 markers with clear and reproducible banding patterns were selected as framework markers. Moreover, 83 pairs of PCR primers described by Lee et al (2004) and Ogundiwin et al (2005) and 62 pairs of microsatellite primers obtained from the database, were used in association with already published linkage maps. The map, with a total of 16 linkage groups (LGs) and covering a total distance of 1100.5 cM was used for QTL analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The nearest AFLP marker, M9E3-11, was a dominant marker present in 'AC2258' (Table 3). Ogundiwin et al (2005) detected 16 QTLs from Phyto.A to P on the RILs derived from the same resistant parent as that we used. Phyt-1 detected on LG7 (pepper chromosome 5) appeared to correspond to Phyto.P detected by Ogundiwin et al (2005), because it was located on the same chromosome.…”
Section: Qtl Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these genetic material did not amplify the SCAR marker OpD04.717, can be used to search for other markers associated with genes that confer resistance to the Oomycete like: CaRGA2, CABPR1, CABGLU, CAPO1, CASC1 (Silvar et al, 2008;Zhang et al, 2013), or QTLs Phyto.4.1, Phyto.5.1, Phyto.6.1, Phyto.11.1 and Phyto12.1, located on chromosomes 4, 5, 11 and 12 respectively (Thabuis et al 2003). Because the resistance to this pathogen is polygenic (Pochard and Daubèze, 1980;Ogundiwin et al, 2005;Minamiyama et al, 2007), it is difficult to explain the resistance to the disease just through marker OpD04.717.…”
Section: Resultados Y Discusiónmentioning
confidence: 99%